Liminality-Ecumenical Space in the Dumia Umbanua Ritual in Kaima Village, North Minahasa - Nikita Sarce Sangian (CV. Rayyan Dwi Bharata, 2023)
This article wants to see how far the ritual role of village governance, which in Tonsea language is called Dumia Umbanua, creates a Limanalytic Space based on the ecumenical movement of church denominations in Kaima Village, North Minahasa Regency. The implementation of this ritual adheres to the concept of the Minahasa local beliefs of the past, making requests to stones, trees, waruga (Minahasa ancestral graves), giving offerings in the form of offerings is a form of teaching that is far different from the Christian-Catholic religious teachings that exist in Kaima Village today. So the act of letting go of religious identity and taking part in rituals by church leaders is the topic of this research. The theory used is Limanality from Victor Turner who sees the influence of ritual implementation to bring parallels between church denominations in a village regardless of majority and minority positions and religious identity. By doing this in practice, the churches formed an ecumenical movement by leaving their respective sacred spaces and entering the profane space and even creating a space of liminality which can be interpreted as a form of ecumenical-liminal space through the implementation of the Dumia Umbanua Ritual.